Identification of Floods in Palembang Area Using Fuzzy Logic Method of Mamdani and Sugeno - Ade Sukmawati; Lemi Iryana; Pandi Adriansyah; Lucky Indra Kesuma (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2023)
Floods are one of the natural events that often occur, especially in areas that have a large population. Palembang is one of the cities in Sumatra Province which often experiences flooding due to its dense population and lack of infiltration areas. One way to improve flood preparedness is to identify floods by using fuzzy logic. This study aims to identify floods in the Palembang area using fuzzy logic mamdani and Sugeno methods. Flood identification is carried out in 6 stages, namely variable determination, fuzzification, inference, application of fuzzy rules, defuzzification, and evaluation. The variables used in this study are rainfall, temperature, area elevation, and the results of flood identification that have a value of flood or not flood. The results of flood identification using the Mamdani method achieved an accuracy of 82% while the Sugeno method achieved an accuracy of 91%. The results of this study indicate that the mamdani and Sugeno fuzzy logic methods are quite good in identifying floods so that they can improve flood preparedness attitudes.